2013
DOI: 10.1001/jama.2013.282190
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Dopamine or Low-Dose Nesiritide in Acute Heart Failure With Renal Dysfunction

Abstract: Small studies suggest that low-dose dopamine or low-dose nesiritide may enhance decongestion and preserve renal function in patients with acute heart failure and renal dysfunction; however, neither strategy has been rigorously tested.OBJECTIVE To test the 2 independent hypotheses that, compared with placebo, addition of low-dose dopamine (2 μg/kg/min) or low-dose nesiritide (0.005 μg/kg/min without bolus) to diuretic therapy will enhance decongestion and preserve renal function in patients with acute heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
250
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 443 publications
(258 citation statements)
references
References 29 publications
1
250
2
5
Order By: Relevance
“…We measured IL‐6, TNF‐α, and hs‐CRP and PTX3 in age and sex‐matched cohorts of HFpEF patients from 3 prospective, placebo‐controlled, randomized clinical trials conducted by the NHLBI Heart Failure Research Network, RELAX (Effect of Phosphodiesterase‐5 Inhibition on Exercise Capacity and Clinical Status in Heart Failure with Preserved Ejection Fraction),37 DOSE (Diuretic Strategies in Patients With Acute Decompensated Heart Failure)38 and ROSE (Renal Optimization Strategies Evaluation) 39. RELAX included S‐HFpEF patients while DOSE and ROSE included acutely decompensated HF (ADHF) patients with both HFrEF and HFpEF.…”
Section: Methodsmentioning
confidence: 99%
“…We measured IL‐6, TNF‐α, and hs‐CRP and PTX3 in age and sex‐matched cohorts of HFpEF patients from 3 prospective, placebo‐controlled, randomized clinical trials conducted by the NHLBI Heart Failure Research Network, RELAX (Effect of Phosphodiesterase‐5 Inhibition on Exercise Capacity and Clinical Status in Heart Failure with Preserved Ejection Fraction),37 DOSE (Diuretic Strategies in Patients With Acute Decompensated Heart Failure)38 and ROSE (Renal Optimization Strategies Evaluation) 39. RELAX included S‐HFpEF patients while DOSE and ROSE included acutely decompensated HF (ADHF) patients with both HFrEF and HFpEF.…”
Section: Methodsmentioning
confidence: 99%
“…26 Low-dose nesiritide as renal adjuvant therapy in patients admitted with ADHF and concomitant renal dysfunction was evaluated in the recently completed Renal Optimization Strategies Evaluation (ROSE) trial. 27 Despite the theoretic benefit of enhancing diuresis and preserving renal function, patients receiving nesiritide had no difference in decongestion or renal function at 72 hours compared with placebo. These data have limited the use of nesiritide to adjunctive therapy with diuretics for dyspnea relief in acute HF.…”
Section: Natriuretic Peptidesmentioning
confidence: 95%
“…A report from the DAD-HF trial of 60 patients with acute decompensated HF found that the combination of dopamine 5 mcg/kg/min plus lowdose furosemide (5mg/h continuous infusion) produced similar urine output as high-dose furosemide (20 mg/h) with reduced risk of worsening renal function (defined as rise in serum creatinine of more than 0.3 mg/dl from baseline to 24 hours; 7 versus 30 percent) [78]. The Renal Optimization Strategies Evaluation (ROSE) trial also tested the hypothesis of whether low-dose dopamine (2mcg/kg/min) (n= 122) would improve urine output and renal function compared to placebo (n= 119) among patients hospitalized with HF and concomitant renal disease [79]. Low-dose dopamine did not improve decongestion or increase renal function when added to diuretic therapy.…”
Section: Inotropesmentioning
confidence: 99%
“…The largest trial, ASCEND-HF, found no change in the outcome of worsening renal function with nesiritide therapy (continuous infusion at 0.01 µg/kg/min with an optional initial loading dose of 2 µg/kg) [82,83]. Similarly, the Renal Optimization Strategies Evaluation (ROSE) trial found that low-dose nesiritide (0.005 µg/kg/min without bolus for 72 h) did not improve decongestion or alter renal function when added to diuretic therapy [79].…”
Section: Vasodilatorsmentioning
confidence: 99%